Cutaneous leishmaniasis: diagnostic pitfall. Case report - Asmae EL Hatimi; Salim Guellouj; Sanae Chehbouni; Kawtar Inani; Hanane Baybay; Fatima Zahra Mernissi (Our Dermatology Online, 2014)
Introduction: Cutaneous Leishmaniasis is a parasitic infection encountered in our daily dermatologic practice. Case report: We present a case of 57 year-old man of Moroccan origin, with erythematous squamous and indurated plaque on the abdomen, treated as sarcoidosis with corticosteroids with no improvement. Discussion: Cutaneous Leishmaniasis is endemic in 88 countries. Aside from its classical presentation it can manifest in multiple different ways. In our case, the diagnostic of Erysipeloide Leishmaniasis was corrected on the basis of the skin smear and the histopathological examination. Our observation is particular in its clinical presentation and location. To our knowledge it is the first Moroccan case. Conclusion: Even in endemic countries it is worth reporting unusual forms and locations of Cutaneous Leishmaniasis in order to avoid inappropriate diagnosis and management.